Crystal and molecular structure of 7-oxabicyclo [2,2,1] hept-5-ene-2,3-exo-dicarboxylic anhydride. - Baggio, S.; Barriola, A.; Konig de Perazzo, P. (American Chemical Society's, 1972)
Fil: Baggio, S. Comisión Nacional de Energía Atómica; Argentina